Optimalisasi Pemanfaatan Media Digital Program Asistensi Mengajar dalam Merumuskan Strategi Inovatif Pembelajaran Matematika - Nafisha, Nabila Angel; Suliyanto (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The Teaching Assistance Program is one form of implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy, which provides space for students to contribute directly to the implementation of learning in schools. This study aims to describe the process of formulating and implementing innovative mathematics learning strategies by students during the implementation of the program at SMP Negeri 22 Gresik, as well as to evaluate its impact on student participation and understanding in grades VII, VIII, and IX. The research used a descriptive approach through observation, daily activity logs, documentation, and feedback from teachers and students. Four learning strategies were applied, namely cooperative learning, game-based learning, contextual approach, and spiral approach, which were reinforced through the use of digital media such as GeoGebra, Quizizz, Wordwall, and so on. The results of the study show that more creative variations in learning methods can increase student engagement, reduce passive classroom interaction, and strengthen the understanding of mathematical concepts that were previously considered difficult, such as algebra and linear equations. Additionally, student integration in school activities strengthens social relationships and provides a comprehensive understanding of educational environment dynamics. These findings confirm that the use of digital technology in teaching assistance programs has significant potential in supporting improvements in the quality of the learning process and can serve as a sustainable model for schools in developing innovative learning strategies.